The effect of the basic tillage system on soybean weediness in the right-bank Forest-Steppe of Ukraine - V. Zadorozhnyi; O. Chernelivska; A. Zadorozhnyi; M. Sokulskyi; A. Labunets (Карантин і захист рослин)
Goal. To improve the system of soybean crops weed control under different methods of tillage.